Стационарные и периодические решения операторного уравнения Риккати со случайным возмущением - Дороговцев, А.Я. (Український математичний журнал, 1993)
Sufficient conditions are presented for the existence of stationary and periodic solutions of the operator Riccati equation under a random perturbation.